Effect of ethanolic extract of Aloe vera (Aloe barbadensis) gel on blood glucose level of alloxan induced hyperglycaemic mice (Bangladesh Journal of Physiology and Pharmacology, 2015)
The purpose of this study was to show the antidiabetic effect of ethanolic extract of Aloe vera gel in alloxan induced hyperglycaemic mice. Ethanolic extract of Aloe vera gel was orally administered for four weeks at a dose of 300mg/kg body weight. Weekly estimates of fasting blood glucose level in normal non-diabetic and alloxan induced hyperglycaemic mice were assessed. Ethanolic Aloe vera gel extract revealed no blood glucose lowering action upon non-diabetic mice. But, a significant reduction in blood glucose level (p